Laparoscopic excision of functional rudimentar cavity for chronic pelvic pain in adolescence - Leite,Sara Dias (2024)
Abstract A female adolescent presented with recurrent pelvic pain, severe dysmenorrhea, and catamenial diarrhea for 2 years. Ultrasound and magnetic resonance imaging suggested a hemi-uterus with a non-communicating rudimentary cavity. Hysteroscopy revealed a normal vagina and cervix, and one tubular uterine cavity with only the left tubal ostium. During laparoscopy, a left hemi-uterus was observed with a normal left ovary and tube, and a non-communicating rudimentary cavity on the right side with normal adnexa (ESHRE/ESGE U4aC0V0). Blood and endometriotic lesions were present at the pouch of Douglas. Excision of the rudimentary cavity, tube, and endometriotic lesions was performed.